ANALISA PENDAPATAN DAN ALTERNATIF PENDAPATAN : IRFAN COLLEGE - Amany Hidayah; Muhammad Munadi (Jurnal Manajemen Pendidikan, 2026)
This study aims to compare the revenue sources of Irfan College (Australia) with educational institutions in Indonesia and to examine the implications of differences in funding structures on the sustainability and quality of educational services. This research employs a qualitative comparative approach by analyzing secondary data, including Irfan College’s financial statements (2023–2024), Indonesia’s School Operational Assistance (BOS) policy, and previous research findings. The analysis was conducted by comparing field findings with theories of educational funding, policy implementation, educational stratification, and street-level bureaucracy. The findings reveal that Irfan College shifted from a 64% reliance on private funding to a 62% dominance of federal grants, effectively reducing public costs. In contrast, the BOS scheme in Indonesia experienced an implementation gap, with 28% of funds misused due to weak human resource capacity. Furthermore, a dualism in public-private funding widened the quality gap, and a negative correlation was found between revenue diversification and the financial performance of PTN-BH (legally-funded state universities) without adequate accountability. This cross-country study compares Australia’s centralized federal funding model with the complexity of hybrid funding in Indonesia. Another novelty is the finding that innovations at the implementation level (digitizing reports and calculating basic education costs) are more effective in addressing school financial governance issues than macro-regulatory changes